SuperNEC antenna and indoor-propagation simulation program. - Fourie, Andre; Nitch, Derek
SuperNEC is a hybrid MoM-UTD antenna and electromagnetic simulation program, developed by Poynting Software (Pty) Ltd. The UTD primitives available in the code are dielectrically coated, multi-faceted plates and elliptical cylinders. The MoM primitives supported are wire segments. The program is capable of running in parallel on a heterogeneous network of processors. A Matlab-based, interactive graphical user interface is used to define the geometry to be simulated, as well as to view the simulation results. The program has been extensively verified using a multitude of test cases, which include comparison to published results and measurements.
Keywords: Indoor radio communication; Moment Methods; Simulation software; Graphical user interfaces; Electromagnetic diffraction; Geometrical Theory of Diffraction (GTD).; Undergound electromagnetic propagation; Computational Electromagnetics (CEM).; Unified Theory of Diffraction (UTD).; Indoor propagation; Hybrid methods